In vitro and in vivo preclinical venom inhibition assays identify metalloproteinase inhibiting drugs as potential future treatments for snakebite envenoming by Dispholidus typus. (June 2022) - Menzies, Stefanie K.; Clare, Rachel H.; Xie, Chunfang; Westhorpe, Adam; Hall, Steven R.; Edge, Rebecca J.; Alsolaiss, Jaffer; Crittenden, Edouard; Marriott, Amy E.; Harrison, Robert A.; Kool, Jeroen; Casewell, Nicholas R.
Abstract: Snakebite envenoming affects more than 250, 000 people annually in sub-Saharan Africa. Envenoming by Dispholidus typus (boomslang) results in venom-induced consumption coagulopathy (VICC), whereby highly abundant prothrombin-activating snake venom metalloproteinases (SVMPs) consume clotting factors and deplete fibrinogen. The only available treatment for D. typus envenoming is the monovalent SAIMR Boomslang antivenom. Treatment options are urgently required because this antivenom is often difficult to source and, at US$6000/vial, typically unaffordable for most snakebite patients. We therefore investigated the in vitro and in vivo preclinical efficacy of four SVMP inhibitors to neutralise the effects of D. typus venom; the matrix metalloproteinase inhibitors marimastat and prinomastat, and the metal chelators dimercaprol and DMPS . The venom of D. typus exhibited an SVMP-driven procoagulant phenotype in vitro . Marimastat and prinomastat demonstrated equipotent inhibition of the SVMP-mediated procoagulant activity of the venom in vitro, whereas dimercaprol and DMPS showed considerably lower potency. However, when tested in preclinical murine models of envenoming using mixed sex CD1 mice, DMPS and marimastat demonstrated partial protection against venom lethality, demonstrated by prolonged survival times of experimental animals, whereas dimercaprol and prinomastat failed to confer any protection at the doses tested. The preclinical results presented here demonstrate that DMPS and marimastat show potential as novel small molecule-based therapeutics for D. typus snakebite envenoming. These two drugs have been previously shown to be effective against Echis ocellatus VICC in preclinical models, and thus we conclude that marimastat and DMPS should be further explored as potentially valuable early intervention therapeutics to broadly treat VICC following snakebite envenoming in sub-Saharan Africa. Graphical abstract: Image 1 Highlights: Snake venom metalloproteinases mediate pathology of Dispholidus typus envenoming. Small molecule drugs were tested for inhibition of D. typus venom in vitro and in vivo . Performance in in vitro experiments did not predict in vivo efficacy. Marimastat and DMPS show potential as novel therapeutics for D. typus envenomation.